Using the situation present assessment method to measure situation awareness in simulated submarine track management. (1st January 2013) - Loft, Shayne; Morrell, Daniel B.; Huf, Samuel
Extant query-based measures of situation awareness that require interruption of dynamic tasks can be inappropriate in certain work contexts. A candidate real-time query-based method, the situation present assessment method (SPAM), was used to examine participants' situation awareness in simulated submarine track management. The simulation and situation awareness queries were based upon a goal-directed task analysis conducted with expert submariners. Participants decided whether to engage enemy vessels using rules based on clear firing corridors for submarine torpedoes, and responded to SPAM queries that assessed their awareness of the current and future display situation. Participants were less accurate and slower to respond to SPAM queries that assessed awareness of the future display situation compared to the current display situation. Consistent with theoretical frameworks of visual sampling and attention-situation awareness integration, the relative predictive utility of current- and future- SPAM queries depended on the nature of the display information relevant to performance goals.